2018
DOI: 10.1177/0269215518792039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aquatic high-intensity interval training on aerobic performance, strength and body composition in a non-athletic population: systematic review and meta-analysis

Abstract: In a non-athletic population, A-HIIT was safe and may have improved aerobic performance and lower limb strength. The exercise interventions were well described and monitoring and reporting of exercise intensity in water was feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
(111 reference statements)
1
17
0
Order By: Relevance
“…Thivel et al reported that HIIT significantly improved the maximal oxygen uptake and reduced body mass, body fat, SBP, DBP, and HOMA-IR in overweight and obese children and adolescents [48]. A metaanalysis conducted by Depiazzi et al found that aquatic HIIT significantly improved the aerobic performance and lower limb strength in a nonathletic population [49]. A metaanalysis conducted by Cao et al found that HIIT versus MICT showed significant improvement in CRF in children and adolescents [16].…”
Section: Discussionmentioning
confidence: 99%
“…Thivel et al reported that HIIT significantly improved the maximal oxygen uptake and reduced body mass, body fat, SBP, DBP, and HOMA-IR in overweight and obese children and adolescents [48]. A metaanalysis conducted by Depiazzi et al found that aquatic HIIT significantly improved the aerobic performance and lower limb strength in a nonathletic population [49]. A metaanalysis conducted by Cao et al found that HIIT versus MICT showed significant improvement in CRF in children and adolescents [16].…”
Section: Discussionmentioning
confidence: 99%
“…Those who have participated in AHIIT studies were predominantly women; hence our review focused on female populations who are believed to have a higher CMR. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…Exercise training conducted in an aquatic environment using a high intensity interval training approach may be an effective and enjoyable method to increase exercise capacity for adolescents with cerebral palsy. 14 The paucity of studies that have attempted aquatic high intensity interval training in adolescents with cerebral palsy means that a number of challenges need to be considered prior to conducting a definitive randomised controlled trial (RCT). 3 For example, the ability to measure the ‘real time’ heart rate responses of participants in water to titrate high intensity is unknown, as is the tolerability of this type of training for this population, and effect of potential physical barriers such as pain.…”
Section: Introductionmentioning
confidence: 99%
“…14 The paucity of studies that have attempted aquatic high intensity interval training in adolescents with cerebral palsy means that a number of challenges need to be considered prior to conducting a definitive randomised controlled trial (RCT). 3 For example, the ability to measure the ‘real time’ heart rate responses of participants in water to titrate high intensity is unknown, as is the tolerability of this type of training for this population, and effect of potential physical barriers such as pain. Further, the feasibility to quantify improvements in aerobic capacity following aquatic interventions in this population using gold standard measures; namely peak rate of oxygen uptake measured during a laboratory based cardiopulmonary exercise test, is unclear, making prospective sample size calculations challenging.…”
Section: Introductionmentioning
confidence: 99%